The beneficial effects of music on vocabulary acquisition in the EFL classroom - Mravinác Péter; Sinka Hilda (2005)
This thesis examines the beneficial effects of music on learning English as a foreign language. After a literature review on this topic I will prove through a classroom research that music can boost a greater vocabulary acquisition than onlya text. My research is based on different tests and a writing task carried out in a primary school in Pilisszentiván. It investigates the effects of music on vocabulary acquisition through an traditional English nursery song. I will demonstrate that songs not only can create a positive learning environment in the classroom but language acquisition could be effectively developed by music.
Keywords: Pedagógusképzés